Intonation and speech technology of the future English language teachers - Berkimbayev, K.M.; Mutanova, D.Yu.; Beisembayeva, A.A.; Tasova, A.B. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
Mastery of speech culture is the main condition for professional success, psychological comfort, moreover it contributes to the integration of the individual into the world community and culture. In this regard, when preparing a specialist in the field of professional and pedagogical language activities, it becomes necessary not only to know the oral and written norms of the literary language (both native and foreign), but also the ability to use expressive means characteristic of a language in the context of intercultural communication. The formation of the sound culture and expressive qualities of speech of the specialist in the field of foreign language is of particular importance, as the teacher's speech is a role model. In this article the complex of didactic means used in the process of speech’s rhythmic-intonational expressiveness training of future foreign language specialists is considered.
Болашақ ағылшын тілі мұғалімдерінің сөйлеу техникасы жəне интонациясы
Интонация и техника речи будущих учителей английского языка
Keywords: psychological features of oral speech; range of voice; pedagogical activity; teacher's ability; language of future English teachers; creative thinking; speech; communicative and speech culture